Income distribution and current account: A sectoral perspective - Jan Behringer; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
We analyse the link between income distribution and the current account through a descriptive analysis for the G7 countries and a series of panel estimations for the G7 countries and a larger sample of 20 countries for the period 1972-2007. We find that, firstly, rising personal inequality leads to a decrease of household net lending and the current account, ceteris paribus. The effect is strong for top household income shares, but much weaker for the Gini coefficient of household income. This finding is consistent with consumption externalities resulting from upward-looking status comparisons. Secondly, an increase in the corporate financial balance leads to an increase in the current account, i.e., consumers do not fully 'pierce the corporate veil'. There is also tentative evidence that the corporate net lending and the current account increase as a result of a decline in the share of wages in value added. The joint effects of changes in personal and functional income distribution contribute to a significant degree to explaining the global current account imbalances prior to the Great Recession.
urn:nbn:de:101:1-2014031110856
Keywords: C23; E2; E21; F32; F41; G3; 330; Income distribution; current account determinants; household saving; corporate saving; panel data analysis